100 YEARS OF VITAMIN D: Historical aspects of vitamin D. Issue 4 (22nd April 2022) - Jones, Glenville
Abstract : Vitamin D has many physiological functions including upregulation of intestinal calcium and phosphate absorption, mobilization of bone resorption, renal reabsorption of calcium as well as actions on a variety of pleiotropic functions. It is believed that many of the hormonal effects of vitamin D involve a 1, 25-dihydroxyvitamin D3 -vitamin D receptor-mediated transcriptional mechanism involving binding to the cellular chromatin and regulating hundreds of genes in many tissues. This comprehensive historical review provides a unique perspective of the many steps of the discovery of vitamin D and its deficiency disease, rickets, stretching from 1650 until the present. The overview is divided into four distinct historical phases which cover the major developments in the field and in the process highlighting the: (a) first recognition of rickets or vitamin D deficiency; (b) discovery of the nutritional factor, vitamin D and its chemical structure; (c) elucidation of vitamin D metabolites including the hormonal form, 1, 25-dihydroxyvitamin D3 ; (d) delineation of the vitamin D cellular machinery, functions and vitamin D-related diseases which focused on understanding the mechanism of action of vitamin D in its many target cells.